Evaluation of a Virtual Reality Simulation System for Porcelain Fused to Metal Crown Preparation at Tokyo Medical and Dental University. Issue 6 (24th August 2018) - Kikuchi, Hirono; Ikeda, Masaomi; Araki, Koji
Abstract : The use of virtual reality simulation (VRS) is a new teaching modality in dentistry, and there is scope for further research evaluating its use under different educational programs. The purpose of this study was to evaluate how VRS with or without instructor feedback influenced students' learning and skills related to porcelain fused to metal (PFM) crown preparation. In this study, forty‐three dental students in their fifth year of study at Tokyo Medical and Dental University, Tokyo, Japan, were randomly divided into three groups: the first group used VRS (DentSim) with the instructor's feedback (DSF) (n=15), the second group used VRS without the instructor's feedback (DS) (n=15), and the third group neither used features of VRS (NDS) (n=13) nor received the instructor's feedback. All the students performed PFM crown preparation under the same setup once a week for four weeks. Total scores, preparation time, and twelve evaluation items were compared among the three groups and four experiments. The total scores of students in the DSF and DS groups were significantly higher than those in the NDS group. The presence of the instructor did not result in significant difference when VRS was used for training, while it shortened the preparation time at early stages. The results of this study suggested that the use of the VRS system improved student training for PFM crown preparation.